Fine needle aspiration cytology of papillary lesions of the breast: How accurate is the diagnosis? - G. M.K. Tse (2018)
Background: Cytological diagnosis of mammary papillary lesions is difficult. Aim: To review the previous cytology diagnosis of 23 papillomas and 11 papillary carcinomas and specific cytological features that may assist in differentiating these entities. Methods: The cytology preparations were reviewed for: (i) overall cellularity; (ii) epithelial cell ball devoid of fibrovascular cores; (iii) background single cells; and (iv) papillary fragments and their morphology. Results: The overall diagnostic accuracy was 59%, atypical rate was 24%, and the error (combined false positive and negative) rate was 17%. For overall cellularity, 6, 14 and 3 cases of papillomas, and 6, 3 and 2 cases of papillary carcinomas showed low, moderate and high cellularity, respectively. Cell balls were present in mild to moderate number in 20 papillomas and 10 papillary carcinomas. The background single cells were absent, or present in low or moderate to high numbers in 7, 10 and 6 papillomas, and 3, 3 and 5 papillary carcinomas, respectively. Papillary fragments were absent, or present in small, moderate or large quantities in 9, 4, 8 and 2 papillomas, and 6, 3, 1 and 1 papillary carcinomas, respectively. There was no demonstrable quantitative difference between papilloma and papillary carcinoma for all these parameters. Qualitatively, the cell balls and single cells showed a higher degree of atypia in papillary carcinoma, and the papillary fragments were more elaborate and slender. Conclusion: Cytological diagnosis of papillary lesions shows a significant error rate with overlapping features. Cellular atypia and fragments with long and slender papillae with ramifying edges favour papillary carcinoma.